АНАЛІЗ ПІДХОДІВ ДО МОДЕЛЮВАННЯ СОЦІАЛЬНОЇ СФЕРИ РЕГІОНУ - Григорук П. М.; Григорук С. С. (International Journal of Innovative Technologies in Economy, 2018)
The article is devoted to the study of issues related to modeling the social sphere of the region. The concept and characteristics of the social sphere are considered, its components are highlighted. The main features of the region as a modeling object are established. A description of the most common approaches to modeling the social sphere of the region is presented, in particular, the use of balance models, models of mathematical programming, models of forecasting dynamics based on the extrapolation of the trend. Special attention is paid to models of comprehensive assessment by integral index. The directions of models application, drawbacks and limitations in their use are presented.